ANALISIS SKEMA PROMOSI PARIWISATA MELALUI TIKTOK TERHADAP MINAT KUNJUNGAN TSUKAMIE NOODLE BANDUNG - Istifany Shabila, Ghina; Putra Saifudin, Mohamad Faizal; Khairunnisa, Nabila; Agustina, Sinta; Novianti, Wini; Gania Khaerunnisa, Zahra; Abdul Rozak, Rama Wijaya (JURNAL MANAJEMEN KULINER, 2024)
The existence of social media in the digital era has an important role in the promotion of various industrial sectors in Indonesia, including the tourism industry. There are many kinds of platforms that can be utilized in the promotion of a tourist destination, one of which is TikTok. TikTok is a culinary center platform where a variety of unique and creative culinary delights are celebrated and promoted, one of which is Tsukamie Noodle Bar culinary. This research aims to see the effectiveness of promoting Tsukamie Noodle Bar culinary tourist destinations through the TikTok platform in attracting tourists to visit. The research method used is a qualitative method, where researchers conduct direct interviews with the manager or owner of Tsukamie Noodle. The final results of the study stated that the manager stated that Instagram was considered easier and more convenient to use as a promotional media, especially in terms of building interactions with audiences thanks to its complete features.